Postembryonic development of nonmarine ostracod Chlamydotheca arcuata (Sars, 1901) (Crustacea: Ostracoda), reared in the laboratory - Diaz, Analia Roxana (2017)
We describe here 8 instars (from A-8 through A-1) of the life cycle of the Cyprididae Chlamydotheca arcuata (Sars, 1901) from hatching to sexually mature individuals. To study the life cycle of this species, we established and maintained in the laboratory cultures from parthenogenetic adult females collected from temporary ponds and a stream in the Buenos Aires province, Argentina. This report provides a description of the chaetotaxy of each limb along with detailed illustrations. The eggs and the carapaces were photographed by scanning electron microscopy. The life cycle of Chlamydotheca arcuata lasted from 80 to 90 days. Females laid subitaneous eggs that hatched asynchronously. The conditions under which the culture was maintained were always the same; but only when the food changed from algae and bacteria to proteins, did the females start to lay many eggs. The food was the key to the development of the juveniles. In the first instars, those being active swimmers, the carapaces have a greater height in front of the first half of the maximum length and taper toward the rear end to become pointed. The appearance and number of the sensory setae on the carapace increase in the latest instars.